Therapeutic and Preventive Use of Video Games in Child and Adolescent Psychiatry: A Systematic Review - Zayeni, Darius; Raynaud, Jean-Philippe; Revet, Alexis (Frontiers in Psychiatry, 2020)
Background Over the past decade, the use of commercial video games and serious games has developed in child and adolescent psychiatry. These games may become relevant alternatives or adjuncts to traditional psychotherapy, providing that their effectiveness is properly established. The purpose of this literature review was to evaluate the effectiveness of serious games and commercial video games in the treatment or prevention of psychiatric disorders in children and adolescents. Methods Medline’s database was used to search articles published between January 2012 and July 2019. The following keywords were used for this search: “Video games” OR “Active video game” OR “serious gaming” OR “Serious game” OR “Exergame” AND “Child mental disorder” OR “Adolescent” OR “Child” AND “Therapy” OR “Prevention”. Only comparative studies which targeted interventions on children and adolescents suffering from psychiatric disorders were included. Results Twenty-two studies, focusing on a wide range of psychiatric conditions, met our inclusion criteria's: 14 evaluated serious games and 8 commercial games. All studies were randomized controlled trials but only two studies compared the intervention game to psychotherapeutic gold standard; other studies used a no-intervention control group or an alternative game as the control group. Eighteen studies reported significant improvements on the symptoms and test scores targeted. Conclusion Serious games and commercially available video games can be an effective trajectory for psychotherapy in child and adolescent psychiatry. However, there is a lack of longitudinal studies which assess the sustained effects of these games, and standards for proper evaluation of their effectiveness are missing.